Application of impedance spectroscopy for studying of charged nanoclusters in impurity-helium condensates - Pelmenev, A. A.; Boltnev, R. E.; Bykhalo, I. B.; Krushinskaya, I. N. (Recent Contributions to Physics, 2015)
A gas jet consisting of a mixture of helium and impurity (~ 1% of H2, N2, Ne, Kr, Xe, etc.) gases was directed onto the surface of superfluid helium (HeII) contained in the glass beaker. During condensation of the impurity particles in the bulk superfluid helium the so–called impurity–helium condensate is formed [1]. Recently in 2013, charges were detected for the first time during destruction of the nitrogen-heliumsamples [2]. For further investigations it was proposed to use methods of the impedance spectroscopy. We used a sensor of planar geometry with two conductive meanders (the sensor capacity was of 7.9 pF).